APLIKASI ERGONOMI PADA PEMBUATAN STANDAR HARD COMPETENCY - Nurmianto, Eko; Ningdyah, Widha Kusuma (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
This paper describes the ergonomic application and the determination of stan-dardized working systems hard competency at PT Atak Otomotif Indometal by using Be-havioural Event Interview (BEI) methods and on the spot direct observation. The standard is made as the reference in determining employee minimum performance. By using standardized hard competency already made and weighted using Expert Choice 9.0 Software, furthermore it has to be evaluated towards employee competency to recognize the gap between the standardized and the real competency. Final results show that the average employee comptency is still below at value 2.8 out of 5 based on Panggabean and Walter scale which means their competency tends to fulfill the employer expectation but it needs to be improved. Besides it has approved theory of Nurmianto and Terbit (20-02) who have found that competence is influenced by four factors i.e training, education, working experience, skills which finally conclude that skills is the most influencing factor among other factors towards competency.